2013
DOI: 10.1504/ijbis.2013.054334
|View full text |Cite
|
Sign up to set email alerts
|

Mining social network data for personalisation and privacy concerns: a case study of Facebook's Beacon

Abstract: Abstract:The popular success of online social networking sites (SNS) such as Facebook is a hugely tempting resource of data mining for businesses engaged in personalised marketing. The use of personal information, willingly shared between online friends' networks intuitively appears to be a natural extension of current advertising strategies such as word-of-mouth and viral marketing. However, the use of SNS data for personalised marketing has provoked outrage amongst SNS users and radically highlighted the iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The results indicated that the firm's age, geographic location, and innovativeness have a significant impact on Twitter adoption by SMEs. Jamal, Coughlan and Kamal (2013) inverted the traditional method to personalisation by conceptualising the restrictions of data mining in social networks by using privacy concerns as the guide. Data was collected in the period of the failed launch of Beacon (third party marketing initiative by Facebook).…”
Section: Factors That Influence Smes To Use Social Media To Adopt E-cmentioning
confidence: 99%
“…The results indicated that the firm's age, geographic location, and innovativeness have a significant impact on Twitter adoption by SMEs. Jamal, Coughlan and Kamal (2013) inverted the traditional method to personalisation by conceptualising the restrictions of data mining in social networks by using privacy concerns as the guide. Data was collected in the period of the failed launch of Beacon (third party marketing initiative by Facebook).…”
Section: Factors That Influence Smes To Use Social Media To Adopt E-cmentioning
confidence: 99%
“…In Saudi Arabia, the subscription rate is 80% of total users of Facebook, 81% of current Facebook subscribers in KSA access the channel on a daily basis, and 76% of social media users in KSA visit Facebook through their smartphones and/or tablets. As a result, firms are starting to make wider use of SNS to build closer links with suppliers and customers [1], [24]. Therefore, many firms have been creating new ways to make profitable use of SNS applications [2].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrates that 93% of social media users think that companies should engage social media in their businesses, while 85% of them believe that companies should interact with customers via social media websites (Cone, 2008;Michaelidou et al, 2011). In fact, businesses around the globe are starting to make wide use of social media to build closer links with suppliers and customers and to connect with employees more successfully (Barnes et al, 2012;Jamal et al, 2013). There are offers of direct links from company websites to Facebook and Twitter (Bunker et al, 2013) which suggests the prospect of replacing physical interaction with virtual proximity (Barnes et al, 2012) that could lead to a wider range of communications and opportunities for businesses and customers.…”
Section: Introductionmentioning
confidence: 99%